AB0020 The Role of Macrophage Migration Inhibitory Factor Gene Polymorphism in Susceptibility to Juvenile Arthritis. (10th June 2014) - Danilko, K.V.; Nazarova, L.; Tselousova, O.; Karimov, D.; Malievskiy, V.; Viktorova, T.
Abstract : Background: Background: Juvenile arthritis (JA) is an umbrella term used to describe the many autoimmune and inflammatory conditions that can develop in children ages 16 and younger. According to the ILAR criteria JA include 7 disease subtypes. It was shown that JA is as a complex trait and some genes are associated with JIA in different populations and subtypes, including macrophage migration inhibitory (MIF) gene. MIF is a lymphokine involved in cell-mediated immunity, immunoregulation, and inflammation. It plays a role in the regulation of macrophage function in host defense through the suppression of anti-inflammatory effects of glucocorticoids. Objectives: The goal of the study was to examine evidence for association of the MIF*-173G>C polymorphism (rs755622) with different clinical variants of JA. Methods: The MIF*-173G>C SNP was studied in 155 children with juvenile arthritis (JA) and 208 healthy individuals, citizens of the Bashkortostan, using real time PCR. Statistical analysis was performed in Statistica v. 6.0 and SNPStats programs. Results: The genotype GG (p=0, 02; OR=1, 74, CI (1, 12-2, 72)) and allele G (p=0, 03; OR=1, 55, CI (1, 06-2, 28)) were found to be the genetic markers of increased JA risk. The earlier age debut of JA (0-6 years) was also was marked by the GG genotype (p=0, 003). The GC or CC genotype were associated with the high JA activity (p=0, 04). SNPStats program analysis indicated the association between the MIF*-173G>C SNP and JA in additive model (p=0, 022, OR=0, 63, 95%CI=0, 42-0, 94), dominant model (p=0, 014, OR=0, 57 95%CI=0, 37-0, 90), but not in recessive model (p=0, 7, OR=0, 79, 95%CI=0, 23-2, 74). Conclusions: Our data demonstrate the association of the polymorphic locus MIF*-173G>C with increased JA risk and clinical variants of the disease in patients from Bashkortostan, Russia. References: Angeles-Han S., Prahalad S. The genetics of juvenile idiopathic arthritis: what is new in 2010? Curr Rheumatol Rep. 2010; 12 (2): 87-93. Hinks A., Cobb J., Marion M.C. Prahalad S., Sudman M., Bowes J., et al. Dense genotyping of immune-related disease regions identifies 14 new susceptibility loci for juvenile idiopathic arthritis. Nat Genet. 2013; 45 (6): 664-669. Donn R., Alourfi Z., De Benedetti F., Meazza C., Zeggini E., Lunt M., et al. Mutation screening of the macrophage migration inhibitory factor gene: positive association of a functional polymorphism of macrophage migration inhibitory factor with juvenile idiopathic arthritis. Arthritis Rheum. 2002; 46: 2402–2409. De Dios Rosado J., Rodriguez-Sosa M. Macrophage Migration inhibitory factor (MIF): a key player in protozoan infections. Int J Biol Sci. 2011; (7) 9: 1239-1256. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3197